Pemberian Makanan Tambahan (PMT) Berbasis Pangan Lokal bagi Balita Bermasalah Gizi - Ratnawati, Ratnawati; Reski, Sepsina; Wahyutri, Endah; Supriadi, Supriadi (Universitas Muhammadiyah Mataram, 2026)
Abstract: The issue of toddlers experiencing stagnant weight gain at posyandu continues to pose a challenge in preventing malnutrition. One promising intervention is the provision of supplementary feeding made from locally available foods that align with community dietary patterns and nutritional requirements. This community service aims to improve the mother nutrition knowledge and weight gain among toddlers with growth faltering at community health centers. The community engagement activity involved administering supplementary food for 14 consecutive days to eight toddlers with no weight gain, consisting of 12 days of nutrient-dense snacks and 2 days of complete main meals. The supplementary food was distributed by posyandu cadres directly to the children’s homes, accompanied by educational sessions on infant and young child feeding practices. Findings revealed an improvement in mothers’ nutritional knowledge from 88% categorized as good to 100% good, alongside an average increase in toddlers’ body weight from 11.68 kg to 11.91 kg. The implementation of locally based supplementary food demonstrates potential in promoting weight gain among toddlers with stagnant growth and serves as a viable model for sustainable nutrition interventions at the posyandu level.Abstrak: Masalah balita dengan berat badan tidak naik (T) di posyandu masih menjadi tantangan dalam upaya pencegahan gizi kurang. Salah satu intervensi yang efektif adalah pemberian Makanan Tambahan (PMT) berbasis bahan pangan lokal yang sesuai dengan kebutuhan gizi dan kebiasaan makan masyarakat. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan ibu balita dan berat badan balita dengan status tidak naik (T) di posyandu melalui pemberian PMT berbasis pangan lokal. Metode pengabdian masyarakat dilakukan dengan memberikan makanan tambahan selama 14 hari kepada 8 balita yang tidak naik berat badannya (T), terdiri dari 12 hari pemberian kudapan bergizi dan 2 hari pemberian menu makan utama lengkap. Pemberian PMT dilakukan oleh kader posyandu dan diantarkan ke rumah balita disertai dengan edukasi terkait pemberian makan bayi dan anak. Hasil menunjukkan peningkatan pengetahuan gizi ibu balita dari 88% baik menjadi 100% baik, peningkatan berat badan balita dari rata-rata 11.68 kg menjadi 11.91 kg. Pemberian PMT berbasis pangan lokal berpotensi meningkatkan berat badan balita dengan status tidak naik (T) dan dapat menjadi model intervensi gizi yang berkelanjutan di tingkat posyandu